Digital Opportunities Within the Aboriginal Teacher Education Program: A Study of Preservice Teachers’ Attitudes and Proficiency in Technology Integration - Dragon, Karon; Peacock, Kim; Norton, Yvonne; Steinhauer, Evelyn; Snart, Fern; Carbonaro, Mike; Boechler, Patricia (Alberta Journal of Educational Research, 2012)
This article explores changes that occurred in preservice teachers' thinking about the use of educational technology in a post-secondary, Aboriginal, elementary teacher education program. The research explores relationships associated with changes in preservice teachers' attitudes and perceived proficiency with technology integration. Quantitative results indicate significant increases in several attitude constructs as well as overall computer proficiency over the course of the project. Supplemental qualitative analysis reveals participants' perception of technology integration as a contributing factor in this positive change. The findings from this study represent a research effort to better prepare teachers to meet the educational needs of Aboriginal students in a 21st century context. Cet article explore l’évolution dans les idées des stagiaires quant à l’emploi des technologies éducatives dans un programme postsecondaire de formation pour enseignants autochtones à l’élémentaire. La recherche porte sur des rapports associés aux changements dans les attitudes des stagiaires et leur perception de leur compétence relative à l’intégration technologique. Les résultats quantitatifs révèlent des augmentations significatives tant dans les attitudes que la compétence technologique globale au cours du projet. Une analyse qualitative supplémentaire indique que la perception des participants quant à l’intégration technologique constitue un facteur contributif dans ce changement positif. Les résultats de cette étude représentent un effort de recherche visant une meilleure préparation des enseignants de sorte à répondre aux besoins pédagogiques des étudiants autochtones au 21e siècle.